The Students Perception on Lecturers Teaching from Teaching Children with Diverse Ability Class Questionnaire - Cendana, Wiputra (English Language Education Study Program, 2020)
One of the most important elements to build in a university is the lecturer. This research aims to find out the students perception in the implementation of course design in the classroom, lecturer performance and given assignments in response to high standard of teaching and learning in the higher education. This research used a survey research. The researcher decides to take Primary Study Program Department as a representative of population in University XYZ. Reliability and validity instrument been analyzed by looking at the item analysis, internal reliability (cronbach alpha), and descriptive statistics. The researcher found the strength in the consistency of learning material with learning contract, new insight of teaching, the use of language that the lecturer used, on time given feedback distribution, material review, the source of theory has been attached in the power point slide, time discipline, well done group work, the compatibility between the assignment and learning contract, given test that enrich students critical thinking and direct observation has given positive contribution towards the theory.